If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(b + -5) + 12 = 5 Reorder the terms: 7(-5 + b) + 12 = 5 (-5 * 7 + b * 7) + 12 = 5 (-35 + 7b) + 12 = 5 Reorder the terms: -35 + 12 + 7b = 5 Combine like terms: -35 + 12 = -23 -23 + 7b = 5 Solving -23 + 7b = 5 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '23' to each side of the equation. -23 + 23 + 7b = 5 + 23 Combine like terms: -23 + 23 = 0 0 + 7b = 5 + 23 7b = 5 + 23 Combine like terms: 5 + 23 = 28 7b = 28 Divide each side by '7'. b = 4 Simplifying b = 4
| 16Y=15(y+13) | | 4f-2=18 | | -107=3+10x | | 0.04(12)+0.01x=0.02(12+x) | | 2x-18=5x+12 | | -7(3x+9)=-21x+63 | | n+21=24 | | 4x+b=3x+7 | | 5(5x-20)=25(x-20) | | 8y-8=37-7t | | 9x^2-18x+5= | | y-6=x | | 8850=x^2-14x+63 | | 4y-9+y+20=5y+20-3y | | .5x=-1.5x+4 | | 20+(-7)= | | m/20+100=460 | | 5-2y=-1.5 | | -22+-35= | | -7-8x=-9x+14 | | 2x-3a+4x+2a-5x=0 | | m/20-100=460 | | m/100-20=460 | | m/100+20=460 | | 16(3x-2)=4(12x+5) | | 6g+2(-6+2g)=1-g | | 3x+a=56x | | x+2x-1=4x+3 | | 11x+20=2x+128 | | 3+3m-1=7m+20-2m | | 36=18x^2 | | 3x+6+7x+4=90 |